Catalytic Enantioselective Synthesis of 4-Amino-1,2,3,4-tetrahydropyridine Derivatives from Intramolecular Nucleophilic Addition Reaction of Tertiary Enamides - Tong, Shuo; Wang, Mei-Xiang (Synlett, 2019)
A general and efficient method for the synthesis of highly enantiopure 4-amino-1,2,3,4-tetradydropyridine derivatives based on chiral phosphoric acid catalyzed intramolecular nucleophilic addition of tertiary enamides to imines has been developed. We have also demonstrated a substrate engineering strategy to significantly improve the enantioselectivity of asymmetric catalysis
Keywords: tertiary enamides; 1,2,3,4-tetrahydropyridines; asymmetric catalysis; chiral phosphoric acid; substrate engineering